Prevalência de hemoparasitos em felinos domésticos da micro região de Uberlândia, Minas Gerais, Brasil e correlação com variáveis epidemiológicas - Pereira, Douglas Alves (2018)
Hemoparasite infection in domestic cats is mainly transmitted by arthropod vectors, such as fleas and ticks. Most infections remain without an accurate diagnosis, due to the fact that these commonly used methods have low sensitivity and specificity. The aim of this study was to evaluate the occurrence of the piroplasmids Babesia and Cytauxzoon spp., hemoplasms Mycoplasma and Ehrlichia spp. in domestic cats of the urban region of Uberlândia-MG, and correlate the occurrence with possible epidemiological factors. A total of 300 domestic cats (Felis catus) were evaluated between May 2017 and May 2018, and data were collected to characterize the study population: sex, breed, age, provenance, habitat and regions of the municipality they belonged to. A volume of 0.2μL of blood were collected from ear-tip peripheral vessels, and blood smears were made to visualize parasitic forms. Infections were observed in blood smears: 3.33% (10/300) Babesia spp.; 0.33% (1/300) Cytauxzoon spp; 3.33% (10/300) Ehrlichia spp., and 1.34% (04/300) Mycoplasma spp. Concomitant infections with Babesia spp. and Ehrlichia spp. 0.67% (02/300), and Babesia spp. associated with Mycoplasma spp. were observed. In the association of epidemiological variables with positivity, five presented a statistically significant difference: race (p<0.0460), origin (p<0.0433), habitat (p<0.0189), access sites 0017) and region (p<0.0045), with the highest prevalence being the eastern region of the urban area of Uberlândia/MG. From the obtained results, it was observed that the hemoparasites are present in the domestic cats of the urban region of Uberlândia/MG, being Ehrlichia spp. the most prevalent, this infers the need for more attention from veterinarians to the health of these animals.